Pengaruh Advertising, Live Streaming, Affiliate Marketing Dan Content Creator Terhadap Purchase Decision Melalui Buying Interest - Nathasya Br Sitepu, Sri; Gunawan, Florencia (Gorontalo Management Research, 2025)
The purpose of this study was to determine the effect of Advertising, Live Streaming, Affiliate marketing, and Content Creator on Purchase decision through Buying interest in Generation Z in Surabaya City. A total of 173 Generation Z living in Surabaya City were sampled in the study, using a non-probability sampling approach, especially those who use Instagram, TikTok and Shopee, have watched live streaming and have shopped via Instagram / TikTok / Shopee. The questionnaire instrument was designed based on the research variables to collect research data. Data analysis using Structural Equation Modeling (SEM). The results of this study indicate that not all endogenous variables affect exogenous variables. Although the value is positive, only two variables have a significant effect. The results found that not all marketing methods can influence someone to make a Purchase decision through Buying interest.